Technology – Based Assessment of Soft Skills in Higher Education - Goran Čubrić; Ivana Salopek Čubrić (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
The importance of soft skills, both for the learning process and employment, is well outlined in a number of documents and strategies. At the moment, digital badges seem to be an important technology that can be used to assess soft skills. Digital badges, or more specifically, Open Badges, provide a whole new way of issuing credentials to individuals that demonstrated certain skill. Furthermore, badges allow individuals to complete with themselves or others, and are good instrument that can motivate continued engagement. Taking all this into concern, it should be pointed out that digital badges have great potential to validate evidences of educational achievements in formal education. This paper describes the 4-phase model SAGRADA, developed within the EU LLP project GRASS, in order to support awarding badges. The whole process is additionally explained trough application case developed at one partner institution. The paper also gives overview of student's reactions towards the whole badging principle and discusses the outcomes.
Keywords: I23; 330; ICT; learning; skills; open badges; research